Comparison of Agitation Incidence in Adult Ambulatory Patients who Underwent Surgery by General Anesthesia Using Desflurane or Sevoflurane - Putri, Andika C.; Nawawi, A. Muthalib; Bisri, Tatang (Perdatin Pusat, 2015)
Postanesthesia agitation is a problem that sometimes occurs in patients who underwent general anesthesia. Thisstudy aims to compare the magnitude of the incident postanesthesia agitationin patienambulatory surgery performedunder general anesthesia with desflurane or sevoflurane use. Research single blinde randomized controlled trial in94 ambulatory surgical patients ASA I. Subjects divided into two groups: group I received desfluran and group IIreceived sevoflurane. Both groups at induction with propofol 2 mg/kg, fentanyl 2 μg/kgBW, atrakurium 0,1 mg/kg, then do laringeal mask airway (LMA) installation. Agitation in patiens assesed since the LMA is removed,the use of anesthetic drugs has beeb stoped, then at minute 5, 10, 15, 20, 25, 30, every five minutes after usingagitation-sedation scale riker. Statistic analysis using Chi-square and Mann-Whitney Test. The results obtainedindicate that the ratio of the incidence of agitation in the recovery room between the desflurane with sevofluranegroups were not statistically significant. Obtained 7 patients experiencing agitation pascaanestesi desflurane groupof 47 samples (14.9%), whereas only 5 patients with agitation of 47 samples sevoflurane group (10.6%). Onepatient from group desflurane assessed his agitation scale 6 (very agitated). The result of comparative magnitudeof the incidence of agitation in the group performed under general anesthesia using desflurance with sevofluranegroup using there is not a statistically significant difference.